Suffering as participation with Christ in the Pauline corpus - Davey, Wesley Thomas 1986- (Lanham Lexington Books, 2019)
Trajectories -- Exegesis -- Canon -- Theology.
Includes bibliographical references
Keywords: Bible -- Theology; Suffering -- Biblical teaching